A randomized, double‐blind, fixed‐dose study comparing the efficacy and tolerability of vortioxetine 2.5 and 10 mg in acute treatment of adults with generalized anxiety disorder. (January 2014) - Mahableshwarkar, Atul R.; Jacobsen, Paula L.; Serenko, Michael; Chen, Yinzhong
<x xml:space="preserve">Abstract</x> Background Vortioxetine is a recently approved multimodal antidepressant with anxiolytic properties in preclinical studies. Objective This double‐blind, placebo‐controlled study assessed the efficacy and tolerability of vortioxetine in subjects with a primary diagnosis of generalized anxiety disorder. Methods Subjects (n = 457) were randomized 1:1:1 to treatment with placebo or vortioxetine 2.5 or 10 mg once daily. The primary efficacy endpoint was reduction in Hamilton Anxiety Scale (HAM‐A) total scores from baseline after 8 weeks of treatment. Key secondary outcomes were changes from baseline in HAM‐A total scores for the 2.5 and 10 mg dose, Hospital Anxiety and Depression anxiety subscore, 36‐Item Short‐Form Health Survey, Sheehan Disability Scale, and Clinical Global Impression‐Improvement Scale score, as well as HAM‐A response rate at week 8. Results Neither vortioxetine dose achieved a statistically significant improvement over placebo on the primary endpoint (least‐squares mean difference ± standard error from placebo: –0.87 ± 0.803 [p = 0.279] for 2.5 mg and −0.81 ± 0.791 [p = 0.306] for 10 mg vortioxetine) or on any secondary efficacy endpoints. Common adverse events (≥5% in either vortioxetine group) were nausea, dry mouth, headache, diarrhea, constipation, and vomiting. Conclusions Vortioxetine 2.5 and 10 mg treatment did not significantly improve generalized anxiety disorder symptoms versus placebo. Vortioxetine was safe and well tolerated in this patient population. Copyright © 2014 John Wiley & Sons, Ltd.